Economic and Environmental Assessment of Integrated Solar Combined Cycle Power Plants: A Comparative Analysis with Standalone Fossil and Solar Technologies - Abobaker Alansaryi; Rabea Mussa (Journal of Scientific and Human Dimensions, 2026)
Integrated Solar Combined Cycle (ISMC) power plants represent a promising hybrid technology that combines concentrated solar power with natural gas-fired combined cycle systems to improve the economic viability and environmental performance of solar thermal electricity generation. This study presents a comprehensive techno-economic analysis comparing ISMC plants with standalone focused solar power (FSP) facilities and natural gas integrated combined cycle (NGIC) plants. A thermodynamic model was developed to simulate hourly operations of a 550 MW ISMC plant comprising a 500 MW NGIC plant and a 50 MW parabolic trough solar field across five representative U.S. locations with varying solar resources and ambient temperatures. The levelized cost of electricity (LCOE) and cost of carbon dioxide reduction (CoD) were calculated under different natural gas price scenarios and financial assumptions. Results demonstrate that integrating a focused solar power field into a natural gas combined cycle decreases the LCOE of solar-generated electricity by 35-40% compared to standalone FSP plants, while providing superior dispatchability. At natural gas prices of $8.5/MMBtu, the ISMC achieves lower CO₂ reduction costs than standalone NGIC plants, with significant environmental benefits when considering carbon emissions. The analysis further reveals that capacity factors, solar resources, ambient temperature variations, and capital cost reductions substantially influence the economic competitiveness of ISMC technology. This work provides essential insights for energy planners considering solar integration in future power generation portfolios in regions with high solar potential.
Keywords: Integrated Solar Combined Cycle; Combined Cycle Power Plants; Concentrated Solar Power; CSP; Levelized Cost of Electricity LCOE